2015
DOI: 10.1038/npjschz.2015.41
|View full text |Cite
|
Sign up to set email alerts
|

The association between antibodies to neurotropic pathogens and schizophrenia: a case-control study

Abstract: Background:Exposure to neurotropic pathogens has been proposed as an environmental risk factor for schizophrenia and can be evaluated by measuring pathogen-specific immunoglobulin G (IgG). Seroprevalence of pathogen-specific IgG reflects prior exposure, whereas IgG levels are associated with reactivity or reinfection. Several studies have examined these parameters in schizophrenia. However, results still remain inconclusive, as several previous studies did not correct for important confounding factors.Aims:To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…It is thus of interest that DeWitte et al did not find an association between levels of antibodies to EBV and a schizophrenia diagnosis. 34 However, as they measured EBNA antibodies (DeWitte L, personal communication) as markers of EBV exposure, their findings are consistent with ours. The consistency of our results with other studies that have measured EBV antibodies in individuals with schizophrenia [35][36][37] is difficult to evaluate without additional information relating to the immune responses to defined EBV proteins.…”
Section: Discussionsupporting
confidence: 84%
“…It is thus of interest that DeWitte et al did not find an association between levels of antibodies to EBV and a schizophrenia diagnosis. 34 However, as they measured EBNA antibodies (DeWitte L, personal communication) as markers of EBV exposure, their findings are consistent with ours. The consistency of our results with other studies that have measured EBV antibodies in individuals with schizophrenia [35][36][37] is difficult to evaluate without additional information relating to the immune responses to defined EBV proteins.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies from Iran arrived at inconsistent results regarding the association between schizophrenia and T. gondii seropositivity . Recent research from other countries failed to show a significant association between schizophrenia and T. gondii infection .…”
Section: Discussionmentioning
confidence: 96%
“… of 38 studies showed that individuals with schizophrenia have an increased prevalence of antibodies to T. gondii ; the overall odds ratio was 2.71 (95% CI: 1.93–3.80). However, other studies failed to demonstrate a significant association between schizophrenia and toxoplasmosis . Several investigators in various parts of Iran have sought to determine the association of schizophrenia with T. gondii seroprevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Results from other groups also support that the increase in antibody levels to several viruses is predictive of an 18–34% increase in the risk of developing schizophrenia [ 122 ] or that anti-CMV and anti-HSV1 antibody levels are significantly increased in schizophrenia patients [ 123 ]. However, others have not found significant differences in antibody titers against the pathogens studied, and therefore do not support the hypothesis that increased exposure to neurotropic pathogens after birth is associated with schizophrenia [ 124 , 125 ]. Other evidences demonstrate that CMV infection is associated to poorer markers in the evolution of schizophrenia.…”
Section: Infection By CMV T Gondii and Other Pathogens In Schizomentioning
confidence: 99%